Pengaruh Harga, Kualitas Pelayanan, dan Lokasi Terhadap Keputusan Pembelian(Studi Kasus Rumah Makan Dutarasa 26 Banjarbaru) - Fawzeya, Nuril; , Edy Purwo Saputro, S.E., MM (2017)
This study aims to determine the effect of price, service quality and location to purchasing decision at Rumah Makan Dutarasa 26 Banjarbaru. This research is a quantitative research, using associative view the relationship between variables and measurement study population are all customers Rumah Makan Dutararasa 26. Sample used method Convinience Sampling. The sample used using Convenience Sampling. Obtained a sample of 100 people from Rumah Makan Dutararasa 26 customers. Techniques of data collection is questionnaire. Before the data is analyzed there should be testing of the data analysis requirements that the test instrument, the classical assumption test and multiple linear analysis test. The results of this study indicate that the location does not affect the purchase decisions on Rumah Makan Dutarasa 26, while the price and quality of service influence on purchase decisions on Rumah Makan Dutarasa 26.